The Submerged, Post-Truth “Island of Happiness” in Michel Houellebecq’s Extension du domaine de la lutte - Keith Moser (Humanities, 2023)
This article proposes a Debordian reading of Michel Houellebecq’s first work Extension du domaine de la lutte that would thrust him into the spotlight as France’s most popular and controversial writer. Specifically, this investigation demonstrates that Debord’s theories are a useful lens from which to analyze Houellebecq’s harsh critique of late capitalism. Owing to a radical paradigm shift in the capitalist paradigm, Debord and Houellebecq posit that we live in a brave new world in which millions of individuals no longer have a frame of reference for distinguishing between commonplace reality and its simulation on a screen. On the informational battlefield where simulations of the good(s) life have proliferated themselves to the brink of replacing the real in the collective imagination of consumer citizens, they illustrate that the timeless search for happiness also seems to be even more fraught with peril in the 21st century.